Ductile-brittle transition behaviour of PLA/o-MMT films during the physical aging process - M. Ll. Maspoch; O. O. Santana; J. Cailloux; E. Franco-Urquiza; C. Rodriguez; J. Belzunce; A. B. Martinez (eXPRESS Polymer Letters)
The ductile-brittle transition behaviour of organo modified montmorillonite-based Poly(lactic acid) films (PLA/o-MMT) was analysed using the Essential Work of Fracture (EWF) methodology, Small Punch Tests (SPT) and Enthalpy relaxation analysis. While the EWF methodology could only be applied successfully to de-aged samples, small punch test (SPT) was revealed as more effective for a mechanical characterization during the transient behaviour from ductile to brittle. According to differential scanning calorimetry (DSC) results, physical aging at 30°C of PLA/o-MMT samples exhibited slower enthalpy relaxation kinetics as compared to the pristine polymer. Although all samples exhibited an equivalent thermodynamic state after being stored one week at 30°C, significant differences were observed in the mechanical performances. These changes could be attributed to the toughening mechanisms promoted by o-MMT.